Moodle incidence on the pedagogical practices under b-learning educative modality (2012)
Moodle platform has served as a technology to support mediation and transformation of teaching practices under B-learning Mode, thus affecting the transformation of pedagogic discourse, the construction of the role of a new tutor and the training of a Licenciado in Basic Education in the Distance Learning Faculty Studies of the Pedagogical and Technological University of Colombia. Based on this topic, this research was based on the characterization on how these practices are determined through the use of MOODLE platform and its sense in human formation through the area of humanities. The action-research and qualitative methodology were used, firstly, resignifying the technological appropriation and its formative sense by the use of info-communicational tools. After that, this research worked on understanding the educational purpose of these practices and its actions by the tutor. The results obtained, recognize the importance of understanding the purpose of pedagogical practices in the field of human science and overcoming cultural obstacles focused on enforcing disciplinary rules that blocked the development of social and individual environment in the formation of future graduates.